To Be or Not to Be …Human? Theorizing the Role of Human-Like Competencies in Conversational Artificial Intelligence Agents - Chandra, Shalini; Shirish, Anuragini; Srivastava, Shirish C. (Journal of Management Information Systems, 2022)
FNEGE 1, ABS 4